"He shouldn't have put it that way!" How face threats and mitigation strategies affect person perception in online tutoring. Issue 3 (2nd July 2016) - Brummernhenrich, Benjamin; Jucks, Regina
ABSTRACT: Instructional strategies such as prompts, requests for clarification, and explicit feedback counter social desires of autonomy and appreciation, i.e., they threaten the face of their receiver. We report an online experiment on how readers perceive instructional face threats and what they accept as appropriate. One hundred and twenty-three participants read an online tutor–tutee discourse that systematically varied the tutor's politeness while containing different types of face threats. Face threats were either mitigated politely or expressed without redress. Participants rated their perception of the tutor and the tutor's contribution, and provided alternative formulations of the presented face threats. Results showed that it is beneficial for tutors to mitigate instructional face threats. This finding deserves attention as the tutor's role does, to some extent, legitimate face threats. The discussion examines how formulations influence person perception. Practical conclusions are drawn for instructional online settings.